Impact on blockchain-based AI/ML-enabled big data analytics for Cognitive Internet of Things environment - Mitra, Ankush; Bera, Basudeb; Das, Ashok Kumar; Jamal, Sajjad Shaukat; You, Ilsun (Computer communications, 2023)
Cognitive Internet of Things (CIoT) supports the organizations to learn from the information (data) arriving from various connected devices, sensors, machines and other sources, and at the same time it inspires intelligence into different business operations, products, customer experiences, and people. Data poising attacks are very serious concerns because they may play a significant factor for businesses and organizations for both financial terms and damaging their reputations, when the Big data analytics on the analyzed data is itself corrupted. To mitigate this issue, in this paper, we suggest a blockchain-based Artificial Intelligence(AI)/Machine Learning(ML)-enabled Big data analytics mechanism for CIoT environment. The comprehensive experimental results have been provided under two circumstances: (1) performance of the ML model under data poisoning attacks and (2) performance of the ML model without data poisoning attacks. In the first case, we show how the data poison attacks can effect the ML model when the data is on some cloud storage (i.e. not in the blockchains), whereas in the second case we show the effect when the data is in the blockchains (i.e., without data poisoning attacks). The experimental results demonstrate that we have significant gains in performance in terms of accuracy, recall, precision and F1 score when there are no data poisoning attacks on the data. Moreover, a detailed blockchain simulation has carried out to demonstrate the practical aspects of the proposed security framework.